Process evaluation of Online Remote Behavioural Intervention for Tics (ORBIT) - Khan, Kareem (2021)
Background: Tic disorder is a highly debilitating condition that is more common in children and young people (CYP) than adults. A parent and therapist-supported intervention called Online Remote Behavioural Intervention for Tics (ORBIT) was developed to meet the demand for behavioural therapy for CYP with tic disorders. Whilst a randomised controlled trial (RCT) assesses overall efficacy, a process evaluation is necessary to establish how and for whom an intervention works.